Egg quality during storage and deposition of minerals in eggs from quails fed diets supplemented with organic selenium, zinc and manganese - Gravena, Rodrigo Antonio [UNESP]; Marques, Rafael Henrique [UNESP]; Roccon, Josiane [UNESP]; Picarelli, Juliana [UNESP]; Hada, Fabricio Hirota [UNESP]; Silva, Janaina Della Torre da [UNESP]; Queiroz, Sandra Aidar de [UNESP]; Moraes, Vera Maria Barbosa de [UNESP] (Sociedade Brasileira de Zootecnia, 2011)
Three experiments with Japanese laying quails were performed aiming to assess the effect of supplementation with minerals in organic form on the egg quality during storage and the deposition of minerals in eggs. The assessments of each experiment were related to one mineral, thus, experiment 1 assessed the supplementation with selenium in 0.35-, 0.70- and 1.05-mg/kg levels of feed; experiment 2, the supplementation with zinc in 50-, 100- and 150-mg/kg levels of feed; and experiment 3, the supplementation of manganese with 60-; 120- and 180-mg/kg levels of feed. All diets were evaluated compared with a control diet without mineral supplementation. Birds were distributed in a completely randomized experimental design, with eight birds per plot and six replicates per treatment. Fifty-five days after the beginning of diets, the yolks of three eggs from each plot were collected for selenium, zinc and manganese quantification, whereas the albumens of three eggs from each parcel were collected for analysis of selenium concentration. Eggs were collected at the last days of the experimental period from each experiment, to be stored at room temperature (28±2 °C) and refrigeration (4 °C) during different periods (0, 10, 20 and 30 days), except for experiment 3, in which eggs were stored at 0, 10 and 20 days. Percentages of albumen and yolk, yolk index, Haugh unit and moisture loss of eggs were evaluated. The supplementation with selenium is able to maintain the egg yolk index unchanged over the storage periods; however, supplementation with zinc and manganese is not effective to keep the quality of stored eggs. Supplementation with selenium and manganese is effective to increase the concentration of these minerals at 328.66% in the albumen and at 74.47% in the yolk, respectively. The different levels of zinc do not change the egg composition.
Keywords: Antioxidants; Coturnix coturnix japonica; enrichment of eggs; Japanese quail; organic minerals